Community corrections officer professional orientation: reintroducing the “passive officer” - Wilson, Amber (Journal of crime and justice, 2025)
Previously, researchers have focused extensively on punitive, welfare, and paternal professional orientations of community corrections officers, frequently employing data collection and analysis efforts that depend on conceptualizing professional orientation as a continuum between surveillance and assistance approaches. Through measurement, analysis, or data interpretation, many studies have failed to consider the presence or prevalence of the passive professional orientation. Using a mixed methods approach, the current study observes a meaningful minority of officers within one state department who adopt a passive orientation, identifies orientation correlates, and explores officers’ interpretations of a passive orientation. Quantitative results suggest that officers’ race, professional background, and tenure are related to their professional orientation. During interviews, officers emphasized that their personal career trajectory, experiences of compassion fatigue and burnout, and ongoing departmental shifts can impact professional orientation. Notably, officers spontaneously reaffirmed the relevance of the professional orientation construct. Research implications from this study include a re-evaluation of how research conceptualizes and measures professional orientation, primarily a shift away from framing professional orientation as existing between two polarized approaches. Policy implications provide guidance for community corrections departments regarding supporting line officers experiencing burnout associated with dual role conflict.